FEATURES OF THE PARADIGM OF FORMATION SPIRITUAL BASIS OF SCHOOLCHILDREN IN CONDITIONS MODERN REFORM SECONDARY SCHOOL (Pedagogy of Higher and Secondary Education, 2004)
In the article the author describes meanings of humanization, humanization of education, humane paradigm, the ways of spiritual formation of a personality.